Indicativos de transtornos alimentares em adolescentes brasileiros abusados sexualmente - Andrade, Júlia Altoé (2022)
Introduction: Eating disorders are part of a wide variety of psychiatric illnesses and mainly affect children and adolescents, characterized by the presence of abnormal eating behaviors. These disorders have a multifactorial origin and may be associated with restrictive diets, negative feelings, harmful family relationships, post-traumatic stress resulting from significant traumas during the individuals' lives, among others. Thus, the study seeks to contribute to a better understanding of the topic addressed, analyzing the factors associated between eating disorders and reports of sexual abuse, since the literature on this topic is still scarce. Objective: To evaluate the association between eating disorders indicators and the family and school context in Brazilian adolescents who have already suffered sexual abuse. Methodology: Data from the 3rd edition of the National School Health Survey were used, which applied self-reported questionnaires to students aged 13 to 15, in the ninth grade, throughout Brazil, in order to assess the state of health and the presence of risk behaviors in this population through the association of socioeconomic aspects and lifestyle habits. Results: There is a positive relationship between socioeconomic status, purgative and compensatory methods, and the presence of violence in the daily life of adolescents with the development of eating disorders in this population. The affective involvement of parents/guardians is an important protective factor, both for violent practices and for mental health and disorders. Conclusion: Adolescents who suffer from different types of abuse tend to be more dissatisfied with their bodies, a fact that contributes to the development of eating disorders, thus, public policies aimed at this issue are needed.